Intimate Partner Violence in the Lives of Urban Wisconsin American Indian Women- a Continuation of Colonial Injustice - (:unkn) unknown (My University, 2020)
American Indian women experience intimate partner violence (IPV) at a disproportionately higher rate than any other population, including during the pregnancy period (Bohn, 2002; Burnette, 2016; Kvinge et al. 1998; Robin et al. 1998). IPV is associated with a range of trauma-related health and mental health impacts. Existing literature largely focuses upon the experiences of violence in the lives of American Indian women living on reservations or in rural areas, even though 70 percent of AI women live in urban areas in the United States. To address this gap, this qualitative study was conducted to deepen our understanding of urban American Indian women’s individual lived experiences with IPV; to better understand their unique health needs after experiences of IPV; and to determine the impacts of IPV on their health and wellbeing. In this critical ethnographic study data from semi-structured individual interviews were collected with 34 AI women survivors living in urban areas in Wisconsin. These data were analyzed using thematic analysis. The study was informed by postcolonial and Indigenous feminist theories to frame our understanding of the contexts in which American Indian women experience IPV. Findings from this study revealed how IPV uniquely manifests in the lives of urban AI women, including during the pregnancy period. Additionally, the COVID-19 pandemic served to exacerbate barriers American Indian women face to help seeking after experiences with IPV. These findings contribute to a critical analysis of the intersecting complexities that impact help-seeking for urban American Indian women. From a postcolonial and Indigenous feminist perspective, the structural barriers that inhibit help seeking for women are deeply rooted in a history of colonization and the intersection of racism, sexism and poverty. This analysis not only fills a gap in the literature but can also contribute to the development of context specific interventions that are urgently needed to ensure that American Indian women obtain the necessary services following experiences of IPV in order to reduce its devastating impacts.
Keywords: American Indian; domestic violence; Indigenous; Intimate partner violence